FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PERDARAHAN POST PARTUM DI RUMAH SAKIT UMUM DAERAH KABUPATEN ACEH TAMIANG - lumbantoruan, mestika; Wandra, dr.Toni; anita, surya (JURNAL HEALTH REPRODUCTIVE, 2016)
This study observer the factor related ton post partum haemorrhage in the General Hospital of Aceh Tamiang 2014. the study is observational analytic case-control study design, in which the group is compared with the control group based on the exposure status. The approach used is retrospective, the population is 81 the women who experienced post partum hemorrhage (cases) and 81 women who did not experienced post partum hemorrhage (controls) who gave birth at hospitals Aceh Tamiang dufing year June 2013 - June 2014, all of which are used as samples. The sample were 162 divided into is AnalyzedÂ  using univariate dataÂ  bivariate and multivariate analyzes. results of the research show that the variables which did not show a significant association (multivariate) with PPH in Aceh Tamiang Hospital in 2014 (p> 0.05) are parity and spacing of pregnancy. Variables that shows significant association (multivariate) with PPH in Aceh Tamiang Hospital in 2014 (p <0.05) are age, anemia, a history of previous bleeding and the ANC. The most dominant variables associated with the incidence of postpartum hemorrhage is anemia (p = 0.000; OR = 7.89) and then successively followed by ANC (p = 0.000; OR = 6.14), age (p = 0.000; OR = 5.33) and a history of previous bleeding (p = 0.002; PR = 3.93). It is strongly advised that the Hospital should give counseling to pregnant women who come to visit in ANC, it is suggested to local government (Department of Health Aceh Tamiang) to organize training for health workers who work in hospitals in Aceh Tamiang especially midwives related to pregnant women, childbirth, haemorrhage.